Evaluation of a mindfulness and self-compassion-based psychotherapy incorporating horses for Veterans who have experienced trauma - William R. Marchand; Ryan Lackner; Amy Hartquist; Lisa Finnell; Elena Nazarenko (Elsevier, 2023)
Objectives: The primary aim of this pilot study was to assess the safety, feasibility, acceptability, as well as preliminary outcomes of a mindfulness and self-compassion-based psychotherapy incorporating horses (PIH) intervention, Whispers with Horses, for Veterans who had experienced trauma. Whispers with Horses was developed as a structured intervention that could be easily replicated for additional studies. If shown to be effective by future rigorous research, the aim is to disseminate a manualized version of the intervention to the field. Design: Prospective open trial. Setting: A large Veterans Administration healthcare system and local equine facilities. Intervention: A six-session PIH intervention that focused on participants developing or enhancing mindfulness and self-compassion skills in the context of an emerging horse-human relationship. Main outcome measures: Safety, feasibility and acceptability were assessed, and psychological instruments were administered. Instruments utilized were the PTSD Checklist for DSM 5 (PCL-V), the Patient Health Questionnaire 9 (PHQ-9), the Positive and Negative Affect Scale (PANAS), the Acceptance and Action Questionnaire II (AAQ-II), and the Physical Activity Enjoyment Scale (PACES). Results: Subjects were 33 Veterans who were 52% male with a mean age of 46 years-old. There were no adverse outcomes to participants indicating the intervention was safe. Participants completed an average of 3.8 sessions with 24% completing all sessions indicating the intervention is feasible to use, and acceptable to, the population studied. The mean PACES score for all sessions together was 110.4, indicating subjects generally enjoyed participation. Preliminary outcome assessments revealed pre- to post-session significant improvements in affect and psychological flexibility for some sessions (p ranging from.001 −0.015). Pre- to post-intervention outcomes indicated significant improvements in depression (p = .003) and psychological flexibility (p = .005). Conclusions: The Whispers with Horses intervention shows promise as a PIH for Veterans who have experienced trauma. More rigorous studies of this intervention are warranted. Also, additional investigations aimed at better understanding mechanisms underlying changes in psychological flexibility are justified.